2017
DOI: 10.1097/nna.0000000000000515
|View full text |Cite
|
Sign up to set email alerts
|

Scope of Practice Barriers for Advanced Practice Registered Nurses

Abstract: Collegial relationships, administrative champions, and persistence are key components to breaking down barriers to advanced practice RN (APRN) practice. This article addresses how Iowa APRNs in a state-sanctioned task force identified barriers for practicing at the top of their licensure in a full practice authority state including defending the right to control the scope of nursing practice in court.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Although state practice barriers are most commonly referenced, APRNs face other practice barriers. Even in FPA states, organizational bylaws and insurance and reimbursement issues continue to be barriers ( Lofgren et al, 2017 ). Federal statutes from the Centers for Medicare and Medicaid Services (CMS) impede APRN practice.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Although state practice barriers are most commonly referenced, APRNs face other practice barriers. Even in FPA states, organizational bylaws and insurance and reimbursement issues continue to be barriers ( Lofgren et al, 2017 ). Federal statutes from the Centers for Medicare and Medicaid Services (CMS) impede APRN practice.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…In addition to state practice regulations that restrict practice authority in reduced and restricted practice states, there are other practice barriers that restrict APRN practice, even in FPA states ( Bosse et al, 2017 ; Hain & Fleck, 2014 ; Hastings-Tolsma et al, 2018 ; Lofgren et al, 2017 ; Peterson, 2017 ). These barriers include federal regulations, such as those from the Centers for Medicare & Medicaid Services (CMS), as well as institutional and organizational policies that inhibit APRN-provided care and services ( Hastings-Tolsma et al, 2018 ; Lofgren et al, 2017 ).…”
Section: Aprn Practice Barriersmentioning
confidence: 99%
“…In addition to state practice regulations that restrict practice authority in reduced and restricted practice states, there are other practice barriers that restrict APRN practice, even in FPA states ( Bosse et al, 2017 ; Hain & Fleck, 2014 ; Hastings-Tolsma et al, 2018 ; Lofgren et al, 2017 ; Peterson, 2017 ). These barriers include federal regulations, such as those from the Centers for Medicare & Medicaid Services (CMS), as well as institutional and organizational policies that inhibit APRN-provided care and services ( Hastings-Tolsma et al, 2018 ; Lofgren et al, 2017 ). Institutional and organizational barriers include bylaws that limit APRN roles and authority, including lack of hospital privileges; issues with provider credentialing; limited clinical, admitting, and/or staff privileges; insurance; and reimbursement issues ( Hastings-Tolsma et al, 2018 ; Lofren et al, 2017 ; Robert Wood Johnson Foundation, 2017 ).…”
Section: Aprn Practice Barriersmentioning
confidence: 99%
“…Non-regulatory barriers to practice also inhibit APRN-provided care and services (Hastings-Tolsma et al, 2018; Lofgren et al, 2017). These barriers relate to hospital privileges, organizational bylaws, insurance and reimbursement issues, and required practice agreements (Hastings-Tolsma et al, 2018; Lofgren et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Non-regulatory barriers to practice also inhibit APRN-provided care and services (Hastings-Tolsma et al, 2018; Lofgren et al, 2017). These barriers relate to hospital privileges, organizational bylaws, insurance and reimbursement issues, and required practice agreements (Hastings-Tolsma et al, 2018; Lofgren et al, 2017). Martin and Alexander (2019) found that APRNs working in rural areas and in APRN-managed private clinics were one and a half to six times more likely to be assessed collaborative practice agreement fees, often exceeding $6,000 and up to $50,000 annually.…”
Section: Introductionmentioning
confidence: 99%